Combined Source-Channel Coding of Images under Power and Bandwidth Constraints. (7th December 2006) - Raja Raja, Nouman Nouman; Xiong Xiong, Zixiang Zixiang; Fossorier Fossorier, Marc Marc
Abstract : This paper proposes a framework for combined source-channel coding for a power and bandwidth constrained noisy channel. The framework is applied to progressive image transmission using constant envelopeM -ary phase shift key (M -PSK) signaling over an additive white Gaussian noise channel. First, the framework is developed for uncodedM -PSK signaling (withM = 2 k ). Then, it is extended to include codedM -PSK modulation using trellis coded modulation (TCM). An adaptive TCM system is also presented. Simulation results show that, depending on the constellation size, codedM -PSK signaling performs 3.1 to 5.2 dB better than uncodedM -PSK signaling. Finally, the performance of our combined source-channel coding scheme is investigated from the channel capacity point of view. Our framework is further extended to include powerful channel codes like turbo and low-density parity-check (LDPC) codes. With these powerful codes, our proposed scheme performs about one dB away from the capacity-achieving SNR value of the QPSK channel.